Corrosion Performance of a Novel Aluminium 6061-Sea Sand Composite Under Electrochemical Method - Surojo, Eko; Triyono, Teguh; Akbar, Hammar Ilham; Pramudi, Ganjar; Triyono; Raharjo, Wijang W.; Agiel, Raiddin Muhamad; Majid, Faishal M.; Seputro, Harjo; Habibi, Ilham (Emerging Science Journal, 2025)
The need for lightweight materials is increasing from year to year. In its application, lightweight and strong materials also need to be corrosion resistant. Corrosion resistance is an important property in automotive, especially in high humidity areas. Al6061-Sea sand material is a novel material that meets the mechanical standards required in the automotive sector. A previous study of Al 6061-sea sand conducted the mechanical properties of the composite. This current research focuses on the development of Al 6061 material with variations in weight fraction of sea sand reinforcement against the corrosion rate under the potentiodynamic method to determine the corrosion resistance of the composite material. The composite fabrication uses the electroless coating method on sea sand and the stir casting method with a melting temperature of 750°C. The agitation process used a four-bladed impeller for 10 minutes at 600 rpm with a stirring depth of ½ of the height of the molten metal. The tests include density testing, microstructure observation, and corrosion rate under the potentiodynamic method using an electrochemical potentiostat. The test result obtained the lowest corrosion rate results in 2% wt sea sand with a corrosion rate of 0.61875 mmpy. The increase in corrosion rate value is directly proportional to the addition of the weight fraction of sea sand.